Structure of Myocardium of Young Rats with Simulated Alimentary Obesity Following the Application of Combined Rhythmic Extreme Cold Effects and Cryopreserved Cord Blood Nucleated Cells - Chernyavskaya, Elena A.; Volina, Victoria V.; Babiichuk, Vladislav G. (Problems of Cryobiology and Cryomedicine, 2018)
To date, a large amount of data has been accumulated, indicating a positive effect of rhythmic extreme cooling (–1200C) and medical products obtained from cord blood, both on different organs, systems, and on the whole body. The histological features of the tissues and blood vessels of the heart were studied in the experimental model of alimentary obesity. The appearance of collagen and elastic fibers of the myocardium of young rats before and after the combined application of rhythmic extreme cold exposures (RECEs) and cryopreserved preparation of cord blood nucleated cells (CBNCs) was histochemically assessed. It has been found that the structural organization of the myocardium of young rats with obesity was characterized by pronounced pathological changes associated with impaired blood circulation. Plethora and thrombosis of blood vessels, diapedemic hemorrhages, the myocardium hypertrophy, interstitial and perivascular edema, focal cardiosclerosis were revealed. To days 7 and 30 after the combined use of 9 sessions of the RECEs and CBNCs, the normalization of the heart morphological structure was noted. In the interstitial connective tissue we have observed a proliferation of fibroblasts, diffuse spread of histiocytes, which indicated the development of processes of neoangiogenesis, less expressed cardiosclerosis, perivascular and interstitial edema. Probl Cryobiol Cryomed 2018; 28(2): 108–119